The mitigating role of tax and benefit rescue packages for poverty and inequality in Africa amid the COVID-19 pandemic - Jesse Lastunen; Pia Rattenhuber; Kwabena Adu-Ababio; Katrin Gasior; H. Xavier Jara; Maria Jouste; David McLennan; Enrico Nichelatti; Rodrigo Carvalho Oliveira; Jukka Pirttilä; Matteo Richiardi; Gemma Clare Wright (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
This paper analyses the distributional effects of the COVID-19 pandemic and related tax-benefit measures in 2020 in a cross-country comparative perspective for five African countries: Ghana, Mozambique, Tanzania, Uganda, and Zambia. We first estimate the impact of the crisis on disposable incomes, how effects vary across the income distribution, and in how far tax-benefit policies stabilized earnings losses. We then evaluate the impact on income-based poverty and inequality and the contribution of discretionary tax-benefit policies in alleviating the shock. Our analysis shows modest increases in headcount poverty rates and inequality, and somewhat larger effects on the poverty gap due to lower relative earnings losses of the poor population at the early stage of the pandemic analysed here. We find very limited stabilizing power of tax-benefit policies overall and automatic stabilizers in particular. This illustrates gaps in coverage for the large informal sector and a general lack of income-related means-tested benefits. Except for the Emergency Social Cash Transfer in Zambia, discretionary tax-benefit policies adopted in response to COVID-19 have had limited impact. Pausing a large school feeding programme in Ghana during lockdown has in turn put additional pressure on households with school-age children.
Additional information: Note: file slightly edited on 7 October and 2 November 2021, in particular to add missing industry titles in three figures in Appendix C.
Keywords: D31; E24; H24; 330; COVID-19; income distribution; poverty; inequality; Africa